Handbook for Assessing and Managing Reservoir Sedimentation (Central Water Commissions, 2024)
Handbook is treated as the important knowledge base that will be helpful to prepare tailored guidelines for specific dam and reservoir. It describes all the elements systematically and comprehensively essential for assessment and management of sedimentinduced problems of the dam and reservoir regularly as well as sometimes need based.